The genetics of lean growth - David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1989)
In recent years, the pork industry has faced numerous challenges. As consumer resistance to fatter meats has increased, the industry has had two options, 1) argue against popular opinion that fat consumption posed a health risk or 2) strive to reduce the fatness of their products. Since the first option is highly unlikely, the NPPC and commodity leaders have moved rapidly, decisively, and aggressively to promote and reposition pork as a vital, healthful part of the U.S. diet. Pork consumption from 1965 to 1985 was reasonably stable (1965, 45 lb; 1985, 44.2 lb). Demand has been stable to declining in recent years. However, Glenn Grimes, University of Missouri economist, says pork consumption increased about 3% last year, despite higher prices and stiff competition. Certainly, pork producers can be proud of what has been accomplished, but to be certain that pork remains competitive, progress must be made in reducing fatness of the pork carcass. Additional concerns for the industry are uniformity of the product, convenience for the consumer, and price competitiveness. New buying systems encourage production of lean, uniform lots of market hogs, often at heavier weights than in previous years. For many producers, this may require a change in breeding and production systems.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Genetic selection; Carcass leanness; Lean growth; Pig